Defiance labour and reflexive complicity: Illusio and gendered marginalisation in DIY punk scenes. Issue 3 (May 2020) - Sharp, Megan; Threadgold, Steven
Since punk emerged in the 1970s as a music genre and subculture it has gained significant academic attention. Punk as a concept now alludes to specific places or scenes, and has been established as a general anti-establishment attitude, as well as an anti-consumerist disposition, with a need to do-it-yourself (DIY). Drawing upon ethnographic and interview data from the east coast of Australia, this article analyses struggles that occur within punk spaces where women and queer identifying punks negotiate historically established male dominance. Punk scenes have the general illusio of being resistant to dominant norms and practices, which is attractive to individuals who feel like outsiders. Yet through symbolic violence, systematic oppression can be perpetrated against those who do not invoke idealised forms of masculinity or femininity. Using the affective transference of gendered norms in punk spaces, we find struggles that are often homogenised in punk research which attends critically to subcultural themes of collectivism and resistance. By unpacking these themes, this article puts forth the concepts of reflexive complicity – where men and women reproduce inequality in punk spaces – and defiance labour – moments of overt challenge to symbolic violence within punk spaces and scenes.